2013
DOI: 10.3390/coatings3040243
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Nanodiamond Coating on Steel

Abstract: Abstract:The hardness, heat conductivity and low friction coefficient of microcrystalline diamond make it a suitable candidate for tribological applications. However, its roughness and high deposition temperature pose significant obstacles to these applications. We have successfully grown nanocrystalline diamond on steel at 400 °C by hot-filament chemical vapor deposition by employing a CrN interfacial layer. Nanocrystalline diamond combines hardness and surface smoothness required in tribological applications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…However, there are many different aspects in the micro-Raman spectra of the single crystal diamond and nanocrystalline diamond films [25]. NCD films can be synthesized by means of CVD method on various types of substrates [26] [27]. In this paper, some practical details in the laser Raman spectra of CVD NCD thin films has been shown.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are many different aspects in the micro-Raman spectra of the single crystal diamond and nanocrystalline diamond films [25]. NCD films can be synthesized by means of CVD method on various types of substrates [26] [27]. In this paper, some practical details in the laser Raman spectra of CVD NCD thin films has been shown.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] The advantages open an important application in the fabrication of novel ND-based composites with more outstanding properties by coating and doping techniques. [5][6][7][8][9][10][11][12][13][14][15][16] Hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) is a widely used high energy explosive. It has occupied a key position in the main charge explosive of warheads and the energetic component of composite propellants.…”
Section: Introductionmentioning
confidence: 99%
“…Some multilayer solutions could mitigate this high thermal stress correctly. We recommend the review by Neto et al [30] that addressed this problem and showed a comparative table of the main intermediate layers shown in the literature, qualifying their diamond quality and adhesion.…”
Section: Introductionmentioning
confidence: 99%